2017
DOI: 10.1159/000477538
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of Verbal Fluency Performance in Frontotemporal Dementia

Abstract: Background/Aims: Verbal fluency is impaired in patients with frontotemporal dementia (FTD) and primary progressive aphasia (PPA). This study explored qualitative differences in verbal fluency (clustering of words, switching between strategies) between FTD and PPA variants. Methods: Twenty-nine patients with behavioral variant FTD (bvFTD) and 50 with PPA (13 nonfluent/agrammatic, 14 semantic, and 23 logopenic) performed a semantic and letter fluency task. Clustering (number of multiword strings) and switching (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,280 publications
(25 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…Another explanation might be that the nature of naming errors differed in each genetic variant. MAPT mutation carriers were relatively more impaired on BNT and semantic fluency compared to letter fluency, whereas GRN performed equally impaired on all language tests, suggesting different underlying mechanisms (e.g., semantic problems versus dysexecutive control) (e.g., [36]. We included all fluency tasks in the language domain, but it has been previously demonstrated that fluency also involves other cognitive functions such as executive functioning and semantic memory.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation might be that the nature of naming errors differed in each genetic variant. MAPT mutation carriers were relatively more impaired on BNT and semantic fluency compared to letter fluency, whereas GRN performed equally impaired on all language tests, suggesting different underlying mechanisms (e.g., semantic problems versus dysexecutive control) (e.g., [36]. We included all fluency tasks in the language domain, but it has been previously demonstrated that fluency also involves other cognitive functions such as executive functioning and semantic memory.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable phenotypic prediction furthermore optimizes the diagnostic process by shortening the current diagnostic delay [47], and is helpful for the patient, caregiver and clinician in knowing what disease presentation and course to expect. Verbal fluency tests are widely used in dementia diagnosis setting [48], and are affected in both presymptomatic [8, 11] and symptomatic FTD [49, 50]. Future research could additionally investigate the use of qualitative assessment of verbal fluency (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the assessment of cognitive decline, these qualitative measures extracted from the SVF performances may be of great interest as well for other neurocognitive disorders affecting verbal ability and executive control such as frontotemporal dementia or primary progressive aphasia [55]. …”
Section: Discussionmentioning
confidence: 99%